O INTRAEMPREENDEDORISMO E A SUA INFLUÊNCIA NAS INOVAÇÕES EM EMPRESAS VAREJISTAS SOB A ÓTICA DOS GESTORES - CAPARROZ, PEDRO MIGUEL LEONATO (2019)
The retail trade in Brazil and in the world is highly competitive and to survive the companies seek to differentiate themselves from its competitors. The innovation is one of the best means to achieve this goal. Innovations should be the biggest goal of the company that seeks facilities for the intrapreneurs feel stimulated to create solutions. As a general objective of the study, it was sought to analyze the influence of the intrapreneurship on the innovations of retail companies from the perspective of managers. In fact, the main theoretical aspects related to entrepreneurship, intrapreneurship, innovation and retailing were presented. As a methodological approach, it was opted for the qualitative research, exploratory type. The research instrument adopted was the in depth interview based on a semi-structured script, which was conducted with six professionals who act or acted as the main business managers in large retail companies in the state of São Paulo. Through the specific objectives, the data obtained and with resupply of the theoretical contribution, five categories of analysis were identified: factors that facilitate the intrapreneurship, factors that hinder the intrapreneurship, practices of stimulate to intrapreneurs, classification of the intrapreneurs practices and/or innovations in according with the 12 dimensions of Sawhney et al. (2007) and results of intrapreneur practices and/or innovations. The analysis of the data occurred through content analysis and the results indicate that the general objectives and specifics could be ratified through the excerpts evidenced through the data collecteds that corroborate the purpose of this study. Therefore, facilitating and hindering factors interact with intrapreneurship, and reflect on innovations. The factors presented, the environment, communication and, above all, leadership deserve special mention, since it was considered the critical success factor due to its importance in the process. Stimulating practices were evidenced fulfilling another specific objective. Finally, the intrapreneur actions were classified according to the radar and the results were evidenced. Thus, it is evident that the innovations are influenced by the actions of the intrapreneurs, either through third party ideas or own. The factors that interfere in the organization, some have greater power to influence, and others not so much, depending on the degree of ancestry that the factor exerts on the intrapreneurship, and these on the innovations. It is concluded that intrapreneurship directly influences innovations in retail companies surveyed from the perspective of their leaders.